Institutional Transformation of Madrasa of Muslim Minority in Thailand - Ismail Suardi Wekke; Muhammad Ashrori; Budianto Hamuddin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2018)
The article discusses the history of madrasa in the Southern Province of Thailand. The Muslim Malay community in Southern Thailand is an inseparable part of the Republic of Thailand. Historically, the Muslim Malay community are indigenous people who have embraced Islam since the 13th century, and even reachedits peak of glory during the reign of Pattani Sultanate. The discussion specializes in the history of madrasa in the region. The study uses historical approach. The article illustrates that the beginning of the emergence of madrasa was motivated by the disagreement among Muslim Malay community against Thai governmental policies. Haji Sulong was the founder of the first madrasa in Southern Thailand in 1933 named “Madrasah Al-Ma’arif Al-Watattaniah Fattani” as a manifestation of his intention to improve the socio-economic welfare of Muslim Malay community through education. Finally, the article discusses the institutional dynamics of Muslim minority madrasa and the development in relation to the identity and capacity of community.